Development of Active Learning-Oriented Textbook of Early Childhood Education Lesson Plan Subject - Wuri Astuti; Mustaji Mustaji; Wahyu Sukartiningsih (SELING: Jurnal Program Studi PGRA, 2018)
The aim of this research is to describe: 1) the result of development of active learning oriented textbook of early childhood education lesson plan subject. 2) the properness of developing of active learning oriented textbook for early childhood education lesson plan subject. The research method that used is the adapted R&D research by Dick&Carrey. The research subject is 70 early childhood education student of State University of Malang. Interview sheets and questionnaire are used as data collecting instrument. Data analysis technique for this research is quantitative descriptive dan qualitative descriptive technique. Research result shows that the developing of this textbook is adjusted by need analysis from users, curriculum and learning plan of Early Childhood Education for semester in State University of Malang. Validation result from the book design expert is 91% and the textbook is valid and proper to be used. The lesson plan validation result is 94.12%, valid and proper to be used. The individual trial result is 89.29%, valid and also proper to be used. The trial result for small group is 90.80%, valid and proper to be used. The conclusion is the textbook is proper to be used in lesson plan of Early Childhood Education classes. Suggestion is a wider trial to evaluate the effectiveness of the textbook.